PENGARUH KONSENTRASI DAN SAAT PEMBERIAN INSEKTISIDA NABATI ( DAUN MIMBA ) TERHADAP HASIL TANAMAN KEDELAI (Glycine max, L . Merrill ) VARIETAS GROBOGAN - SETIE HARIENI (JURNAL ILMIAH AGRINECA, 2015)
Research with the aim to determine the Effect of Concentration and Botanical Incecticide (neem leaf) On the Yield ofÂ  Soybean (Glicine max, L Merrill) Variety Grobogan, have been performed in Kalurahan Ledok, Argomulyo, Salatiga. The research method used was a factorial study method RAKL (Completely Randomized Design) with 12 combinations of treatments and 3 replications. As for the treatment factor K0: Without treatment (control) K1: neem leaf extract 150 ml / liter, K2: neem leaf extract 300 ml / liter. Spraying intervals A1: 30 days (30,37,44,51), A2: age 37 days (37,44,51,58), A3: age 44 days (44,51,58,65), A4: age 51 days (51,58,65,72). The result study showed that the concentration of neem leaf treatment was not significantly different in plant height, stover fresh weight, dry stover weight, seed weight per plot and weight of 100 dry seeds but significant reducing the intencity of pests and the percentage of infected plants. The best results on the highest weight of 100 seeds on KOA4 (20.156 g), seed weight per plot K2A1 (546.67 g)